Using GRACE to Improve Altimetry's Ocean De‐Aliasing Model. Issue 1 (21st January 2022) - Bonin, J. A.; Save, H.
Abstract: We demonstrate that daily Gravity Recovery And Climate Experiment (GRACE) data can be used to improve the non‐tidal Dynamic Atmospheric Correction (DAC) used to de‐alias Jason altimetry and reduce high‐frequency errors. To accomplish this, we compute empirical orthogonal function (EOF) maps based on the ocean‐model part of the DAC, then fit the GRACE and Jason data to those maps. The resulting DAC and GRACE EOF time‐series are compared to the altimetry EOF time‐series, to determine which best represents the state of the ocean. We find that, for the first six modes in the North Pacific, 19 modes in the Southern Ocean, and three modes in the combined Indian/Atlantic/Equatorial‐Pacific region, GRACE is able to explain more of the 10–20‐day altimetry signal than the original de‐aliasing model can. We recombine these first GRACE modes with the remaining ocean‐only DAC data to produce an improved 10–20‐day model during times when GRACE data exists. We smoothly blend that series with the original model during times when there is no GRACE data, also restoring the faster frequencies from the original. The result is a blended model which explains 10%–30% more of altimetry's 10–20‐day variance in the Southern Ocean than the original DAC model did, 5%–10% more in the Atlantic and Indian Oceans, and is functionally equivalent in the Equatorial Pacific. The removal of the additional sub‐Nyquist‐frequency signals will result in better Jason altimetry data with fewer aliased signals incorrectly propagated to longer periods. Plain Language Summary: We combine an experimental version of GRACE satellite gravity data with the older Mog2D ocean model, to produce a blended model which is better for de‐aliasing satellite altimetry data. We use an empirical orthogonal function method for signals with periods between 10 and 20 days, in combination with Jason satellite altimetry data, to determine which pieces of the GRACE signals are better than the original model. We then recombine the series, filling in the best parts of GRACE, but keeping the original model in the places and frequencies where GRACE cannot improve things. The final blended model is able to explain 10%–30% more of altimetry's high‐frequency signal in the Southern Ocean, with lesser improvements everywhere else in the ocean. Key Points: For periods 10–20 days long, Gravity Recovery And Climate Experiment (GRACE) gravity data can improve upon altimetry's ocean de‐aliasing model over much of the ocean An empirical orthogonal function (EOF) reconstruction technique is used to combine gravity and model data over the 10–20 days frequency band The new model better de‐aliases the sub‐20‐day altimetry data than the original, explaining up to 30% more altimetry signal